2005
DOI: 10.4049/jimmunol.175.1.270
|View full text |Cite
|
Sign up to set email alerts
|

The CD3ε Proline-Rich Sequence, and Its Interaction with Nck, Is Not Required for T Cell Development and Function

Abstract: The CD3ε proline-rich sequence (PRS) binds to the cytosolic adaptor molecule Nck after TCR ligation. It has been proposed that this interaction is essential for immunological synapse formation and T cell activation. To assess the physiological importance of the CD3ε PRS, we have generated mice that lack this motif (CD3ε.PRSM). Pull-down experiments demonstrated the inability of Nck to bind to the CD3ε PRS in thymocytes from mutant mice after TCR ligation. Surprisingly, no differences were observed in the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 46 publications
(37 reference statements)
1
68
2
1
Order By: Relevance
“…No gross abnormalities were observed in the distribution of thymic populations, in accordance with our observation that the conformational change is not elicited during positive selection. Unfortunately this system does not offer information regarding the role of the CD3 proline-rich sequence in negative selection because it was not studied in transgenic TCR models (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No gross abnormalities were observed in the distribution of thymic populations, in accordance with our observation that the conformational change is not elicited during positive selection. Unfortunately this system does not offer information regarding the role of the CD3 proline-rich sequence in negative selection because it was not studied in transgenic TCR models (27).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the CD3 proline-rich sequence in thymic development has recently been brought into question (27). Bone marrow chimeras in CD3 -deficient mice have been used to express a CD3 mutated in the proline-rich sequence before studying T cell development.…”
Section: Discussionmentioning
confidence: 99%
“…Systems using 293T transfected cells such as Phoenix (Phoenix-Ampho, American Type Culture Collection (ATCC) SD3443) and Eco (ATCC: SD 3444), which can be directly transfected, are most commonly used. However, our lab has successfully used a 3T3-based cell line, GP+E86 (ATCC: CRL-9642) 7,11,14 . The two-step process we describe here first generates retrovirus by the transient transfection of 293T cells with three plasmids, to minimize the possibility of generating replicationcompetent retrovirus (RCR) 15,16 .…”
Section: Generation Of Retroviral Producer Cell Linesmentioning
confidence: 99%
“…Bone marrow reconstitution with CD3ε PRS mutants in CD3ε-deficient mice, Nck overexpression in primary T cells, Nck knockout mice, and PRS knockin (KI) mice have all been used to study the role of the PRS and Nck in T cell development and mature T cell activation (14)(15)(16)(17)(18)(19)(20). Some experiments have suggested that the PRS is important for thymic maturation, but not for mature T cell activation in vitro (15), although experiments with bone marrow chimeras indicate that the PRS is important to activate mature T cells by weak, but not by strong, agonists in vitro (19).…”
mentioning
confidence: 99%